2008
DOI: 10.1007/s10528-007-9136-4
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the Matrix Metalloproteinase-2 Gene Promoter is Associated with Cervical Neoplasm Risk in Mexican Women

Abstract: Matrix metalloproteinase-2 (MMP-2) is an enzyme with proteolytic activity on matrix proteins, and previous studies have revealed a strong association between the MMP-2 -1306C-->T polymorphism and the risk of several types of cancer. Our study looked at whether this polymorphism contributed to the development of cervical neoplasia by analyzing 54 patients with invasive squamous cell cervical cancer, 100 patients with cervical intraepithelial neoplasia, and 126 control subjects. The MMP-2 CC genotype was more fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…After amplification, the purified 4 µl PCR products were subjected to restriction digestion by Eco RI restriction endonuclease (Fermentas, Vilnius, malignancies has been demonstrated. [13][14][15][16][17][18][19] MMP-2 (gelatinase A) has type IV collagenolytic activity and is constitutively expressed by most connective tissue cells including endothelial cells, osteoblasts, fibroblasts and myoblasts. The membrane-bound activation of pro-MMP-2 through its proteolytic activity against components of the basement membrane executes extracellular matrix remodeling as well as uniquely generates several different biologically active molecules including laminin, fibronectin, and monocyte chemoattractant protein-3.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…After amplification, the purified 4 µl PCR products were subjected to restriction digestion by Eco RI restriction endonuclease (Fermentas, Vilnius, malignancies has been demonstrated. [13][14][15][16][17][18][19] MMP-2 (gelatinase A) has type IV collagenolytic activity and is constitutively expressed by most connective tissue cells including endothelial cells, osteoblasts, fibroblasts and myoblasts. The membrane-bound activation of pro-MMP-2 through its proteolytic activity against components of the basement membrane executes extracellular matrix remodeling as well as uniquely generates several different biologically active molecules including laminin, fibronectin, and monocyte chemoattractant protein-3.…”
Section: Study Populationmentioning
confidence: 99%
“…In fact, it has been shown in various studies that frequency of −1306 MMP-2 (C/T) polymorphism is significantly higher in patients of lung cancer, gastroesophageal cancer, breast cancer, invasive bladder cancer and cervix cancer. [13][14][15][16][17][18][19] The data on strength of association between −1306 MMP-2 polymorphism and glioblastoma multiforme (GBM) in Indian population are not available. Therefore, the present study was carried out to look for the association of MMP-2 gene polymorphism with susceptibility of developing glioblastoma in Indian population.…”
Section: Introductionmentioning
confidence: 99%
“…Low-risk HPV types include types 6, 11, 42, 43, and 44. High-risk HPV types include types 16,18,31,33,34,35,39,45,51,52,56,58,59,66,68, and 70. Infections with low-risk types can cause benign or low-grade cervical cell changes, genital warts, and recurrent respiratory papillomatosis (27,28).…”
Section: Hpv Infection In Uterine Cervical Carcinomamentioning
confidence: 99%
“…During the last decades progress in research on enzyme activities showed the potential significance of MMP-2 and MMP-9 in the progression of cervical uterine cancer suggesting their prognostic value (14,15,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Sheu et al demonstrated that MMP-2 and MMP-9 were overexpressed in >90% of squamous cell carcinomas (SCC) and 83-100% of HSIL, but were less frequently expressed in LSIL and normal squamous epithelium (13%).…”
Section: Mmps In Uterine Cervical Neoplasmmentioning
confidence: 99%
“…40 Furthermore, polymorphisms in MMP2 in nonsmokers, and MMP12 and MMP13 in smokers, have been linked to gastric cardia adenocarcinoma in a high-incidence region of north China. 41 In a large meta-analysis, Peng et al found that MMP2 (-1306C>T and -735C>T) and MMP7 -181A>G polymorphisms play allele-specific roles in cancer development, while the MMP9 -1562C>T polymorphism did not appear to be a major risk factor for cancer.…”
mentioning
confidence: 99%